A Novel Algorithm for Determining Contact Area Between a Respirator and a Headform. - Lei, Zhipeng; Yang, James; Zhuang, Ziqing (Journal of Occupational & Environmental Hygiene, 2014)
The contact area, as well as the contact pressure, is created when a respiratory protection device (a respirator or surgical mask) contacts a human face. A computer-based algorithm for determining the contact area between a headform and N95 filtering facepiece respirator (FFR) was proposed. Six N95 FFRs were applied to five sizes of standard headforms (large, medium, small, long/narrow, and short/wide) to simulate respirator donning. After the contact simulation between a headform and an N95 FFR was conducted, a contact area was determined by extracting the intersection surfaces of the headform and the N95 FFR. Using computer-aided design tools, a superimposed contact area and an average contact area, which are non-uniform rational basis spline (NURBS) surfaces, were developed for each headform. Experiments that directly measured dimensions of the contact areas between headform prototypes and N95 FFRs were used to validate the simulation results. Headform sizes influenced all contact area dimensions (P< 0.0001), and N95 FFR sizing systems influenced all contact area dimensions (P< 0.05) except the left and right chin regions. The medium headform produced the largest contact area, while the large and small headforms produced the smallest.